Novel cinnamic acid–tryptamine hybrids as potent butyrylcholinesterase inhibitors: Synthesis, biological evaluation, and docking study. Issue 10 (4th October 2018) - Ghafary, Shahrzad; Najafi, Zahra; Mohammadi‐Khanaposhtani, Maryam; Nadri, Hamid; Edraki, Najmeh; Ayashi, Neda; Larijani, Bagher; Amini, Mohsen; Mahdavi, Mohammad
Abstract: A novel series of cinnamic acid–tryptamine hybrids was designed, synthesized, and evaluated as cholinesterase inhibitors. Anticholinesterase assays showed that all of the synthesized compounds displayed a clearly selective inhibition of butyrylcholinesterase (BChE), but only a moderate inhibitory effect toward acetylcholinesterase (AChE) was detected. Among these cinnamic acid–tryptamine hybrids, compound7d was found to be the most potent inhibitor of BChE with an IC50 value of 0.55 ± 0.04 μM. This compound showed a 14‐fold higher inhibitory potency than the standard drug donepezil (IC50 = 7.79 ± 0.81 μM) and inhibited BChE through a mixed‐type inhibition mode. Moreover, a docking study revealed that compound7d binds to both the catalytic anionic site (CAS) and the peripheral anionic site (PAS) of BChE. Also, compound7d was evaluated against β‐secretase, which exhibited low activity (inhibition percentage: 38%). Abstract : Novel cinnamic acid–tryptamine hybrids were designed, synthesized, and evaluated as cholinesterase inhibitors. All of the synthesized compounds displayed selective inhibition of butyrylcholinesterase (BChE) but only a moderate inhibitory effect toward acetylcholinesterase was detected. Compound7d was found to be the most potent inhibitor of BChE with an IC50 value of 0.55 ± 0.04 µM and a 14‐fold higher inhibitory potency than the standard drug donepezil.